2004
DOI: 10.1016/s0006-3495(04)74311-8
|View full text |Cite
|
Sign up to set email alerts
|

Rho Mediates the Shear-Enhancement of Endothelial Cell Migration and Traction Force Generation

Abstract: The migration of vascular endothelial cells in vivo occurs in a fluid dynamic environment due to blood flow, but the role of hemodynamic forces in cell migration is not yet completely understood. Here we investigated the effect of shear stress, the frictional drag of blood flowing over the cell surface, on the migration speed of individual endothelial cells on fibronectin-coated surfaces, as well as the biochemical and biophysical bases underlying this shear effect. Under static conditions, cell migration spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 37 publications
(64 reference statements)
8
121
1
Order By: Relevance
“…Many laboratories are attempting to determine how motility-related signals might be connected (often in two-way fashion) to the proximally governing biophysical mechanisms (22,27,28). Because of the great complexity of biochemical signaling networks and of their connections to biophysical mechanisms by which cell functional responses such as motility are conducted (29), we are convinced that construction of cell signal-response models will require multivariate computational analysis (30, 31).…”
Section: Resultsmentioning
confidence: 99%
“…Many laboratories are attempting to determine how motility-related signals might be connected (often in two-way fashion) to the proximally governing biophysical mechanisms (22,27,28). Because of the great complexity of biochemical signaling networks and of their connections to biophysical mechanisms by which cell functional responses such as motility are conducted (29), we are convinced that construction of cell signal-response models will require multivariate computational analysis (30, 31).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, cell migration shows a maximum speed at the intermediate level of adhesiveness [Duband et al, 1991;DiMilla et al, 1993;Keely et al, 1995]. We have shown that EC migration on fibronectin (0.5-40 mg/cm 2 ) has a biphasic dependency on the density, with highest migration speed at $5 mg/cm 2 [Shiu et al, 2004]. Shear stress increases the migration speed at both high and low densities, suggesting that shear stress may enhance the adhesion at the front on the low fibronectin density and the detachment at the rear on the high fibronectin density.…”
Section: Ecm In Mechanotransductionmentioning
confidence: 75%
“…In addition, inhibition of Rho blocks directional migration under flow, but enhances migration speed, possibly by decreasing cell-ECM adhesions [Wojciak-Stothard and Ridley, 2003]. Since complete inhibition of Rho or p160ROCK disrupts actin filaments and inhibits EC migration Shiu et al, 2004], a medium level of Rho activity may be needed for the most efficient EC migration. Rho activity is also required for the generation of traction force through actin fibers and cell-ECM adhesions in response to shear stress [Shiu et al, 2003] (see the section on ''Roles of Integrins and Proteoglycans in Shear StressInduced EC Migration'').…”
Section: Cytoskeleton As Mechano-effectormentioning
confidence: 99%
“…External forces can cause adhesion reinforcement (17)(18)(19) and stress fiber formation (20) to strengthen traction forces and appear to initiate specific signaling pathways that may provide feedback to regulate myosin activity (3,21). Thus, it remains unclear whether external forces act directly or also depend on mechanically induced changes in traction forces to exert their cellular effects.…”
mentioning
confidence: 99%